Construction of a tephra-based multi-archive coherent chronological framework for the last deglaciation in the Mediterranean region. (15th July 2019) - Bazin, L.; Lemieux-Dudon, B.; Siani, G.; Govin, A.; Landais, A.; Genty, D.; Michel, E.; Nomade, S.
Abstract: Proxy records from different climate archives such as ice cores, speleothems or sediment cores are essential to define the sequence of events over to the last deglaciation. However, multi-archive comparison and compilation of data, necessary to assess the robustness of climate models, are rapidly limited by inconsistencies between archives' chronology. Here we present the development and validation of the Datice chronological integration tool for the construction of multi-archive coherent chronologies. This chronology building tool, first developed to date ice cores only, can now integrate deposition-like archives such as sediment cores and speleothems, independently or coherently. The robustness of this dating method resides in its capacity to build coherent chronologies for multiple archives with a proper calculation of chronological uncertainties. Using this tool, we were able to construct a coherent chronology for the last deglaciation in the Mediterranean region based on volcanic tephra layers correlation in terrestrial and marine sediment cores. We confirm the synchronicity, within chronological errors, of the sequence of events characterizing the last deglaciation between Greenland and the Mediterranean region, independently of any climatic alignment assumptions. Using this chronological framework, we however highlight some regional expression of this transition period in term of vegetation cover over the Mediterranean region. Highlights: Multi-archive coherent chronology for the last deglaciation in the Mediterranean region. Volcanic-based synchronization, independent of climatic alignment assumptions. Regional expression of vegetation changes during the last glacial-interglacial transition.